Analysis of Factors Affecting the Incidence of Stunting in Children 24-59 Months in 2023 - Rosdiana; Marhtyni; Baktiana Ratna Etnis (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Stunting is a chronic condition where the body becomes very short for the age it should be measured based on Body Length according to age (PB/U) or Height according to age (TB/U) with values on anthropometric tables <-2SD according to international references. Objective: This study aims to analyse the factors that influence the incidence of stunting in toddlers. Method: This research is observational using a Cross-Sectional Study design. A total of 87 samples were taken through Simple Random Sampling. Data collection was done through observation, interviews, and documentation. Data were analysed with the SPSS program, statistical tests using Chis- Square for bivariate tests, and logistic regression tests for multivariate tests with p < 5%. Results: showed that the environmental sanitation variable X2 hit value 13.104 > from 3.841 and p value 0.000 < 0.05, LBW X2 hit value 14.303 > from 3.841 and p value 0.000 < 0.05, Immunisation X2 hit value 4.44 > from 3.841 and p value 0.03 < 0.05 and History of infectious disease X2 hit value 21.60 > from 3.841 and p value 0, 000 < 0.05 this means that all variables affect the incidence of stunting in toddlers but the most influential based on multivariate analysis of the variable history of infectious disease significant value > 0.05 (variable p < 0.05) but the smallest is the history of infectious disease with a p value of 0.00. Conclution: Maximising programs to minimise the occurrence of stunting such as immunisation in accordance with national standards and health promotion related to the prevention of infectious diseases in children needs to be improved to overcome the problem of stunting toddlers.